YIELD STABILITY EVALUATION FOR BREAD WHEAT GENOTYPES UNDER ENVIRONMENTAL VARIATIONS - Al-Falahi, M. A. H.; Dawod, Kh. M.; Omer, Fathi. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to evaluation the yield stability of twenty bread wheat genotypes that cultivated at two locations (fields of the College of Agricultural Engineering Sciences of Duhok and Zenawa district) during the 2019 - 2020 with two planting dates in each location using randomized complete block design with three replications. The results of the combined analysis of variance showed that the mean square for each of the environments, genotypes and their interactions were highly significant for all studied traits, and the variations due to the environments were greater than those of each of the genotypes and the interactions for most of the studied traits. The values ​​of broad sense heritability ranged between 44.44% for spike length and 93.27% for grain weight per spike. The results of the stability parameters showed that the genotype Apst-12-85578 was highly stable for grains weight per spike and final grain yield followed by each of Adana, Bora, and Apst-6-85576 genotypes which showed high stability for the grain yield.